Analisis Kualitas Air Sungai Lasolo di Kecamatan Kendari Barat Kota Kendari - Maharani, Maharani; Rosdiana, Rosdiana; Ndibale, Wa (Universitas Muhammadiyah Kendari, 2023)
This study aims to analyze the quality of the Lasolo river water, compare it with the quality standard for class I PP Number 22 of 2021, and determine the Status of Water Quality using the Pollution Index (IP) method according to the Minister of Environment Decree Number 115 of 2003. Water quality measurements were carried out at 4 points while the parameters measured were pH, TSS, and Fecal Coliform. Based on the data, it was found that the water pH parameter fluctuated between 7.0 to 7.8 obtained at points ST1 to ST4 under normal conditions, which explained that Lasolo River water met the established quality standards. An increase in the TSS parameter is shown at each point with an average of 70-74 mg/L range, which explains that the TSS value exceeds the maximum water quality standard limit of 40 mg/L. In contrast, the Fecal Coliform parameter at each sampling point has a measurement value of 0 MPN/100 mL, which means it is below the standard quality limit of 100 MPN/100 mL. The water quality status of the Lasolo River was determined using the Pollution Index (IP) method and found that all sampling points were in